Estratégia de controle Volt/VAr Coordenado para sistemas de distribuição inteligentes - Mello, Ana Paula Carboni de (2018)
This work presents contributions to the study and development of Voltage and Reactive Power Control (Volt/VAr control or VVC) for intelligent distribution systems. Currently, the use of VVC is considered one of the most important and desired functions in the context of distribution systems modernization, in view of the rise of communication technologies and new controllable equipment. In this sense, some commercial solutions have been proposed in the last years for the implementation and optimization of VVC in the distribution networks. However, studies and propositions of adequate techniques are still necessary, since most of these solutions have not yet considered the possibility of controlling voltage levels by frequency inverters, excluding the participation of distributed generation, static reactive compensators and other electronic equipment with potential benefits of VVC in distribution networks. In this context, this work proposes a new VVC methodology to coordinate the traditionally equipment actions with power electronics equipment, ensuring the voltage control at adequate levels mainly with operational gains in relation to the reduction of the number of commutations of conventional devices. For this, a coordinated centralized VVC strategy is proposed in the substation that considers the limitations of the different equipment and the commutations proportionality without impairing the voltage levels. The methodology was applied in two distribution systems based on real IEEE networks, which was implemented through an interface between the software MATLAB® and OpenDSS® with satisfactory results.